Russian Club Life - Nadezhda Azhgikhina (Studies in 20th & 21st Century Literature, 2000)
While the 1990s in Russia witnessed a marked decrease in the officially sponsored clubs that organized Soviet citizens' leisure hours along ideologically approved collective lines, they also ushered in a host of new, diverse clubs closer to Western models. The broad range encompassed political, business, professional, and sports clubs, as well as health clubs, the night clubs that received bemused coverage by the Western press, and the clubs created primarily by and for the New Russians. Among the last, the exclusive English Club, which ruled as Moscow's premier club, combined stylish relaxation amidst lavish surroundings with a more covert agenda: the establishment of useful business and political contacts. With the formation of a stable oligarchy as its goal, the club reflected the decade's penchant for self-legitimation through a revival of elitist tsarist traditions.
Keywords: clubs; club life; Russian clubs; Western clubs; political clubs; business clubs; professional clubs; sports clubs; health clubs; New Russians; English Club; tsarist tradition